The Influence of Leadership and Organizational Culture on Employee Work Satisfaction in Bolmut Regency - Pati, Agustinus (AIBPM Publisher, 2019)
This study aims to analyze the influence of leadership and organizational culture on job satisfaction. This study uses explanatory research or hypothesis testing research. The location of the study was carried out in the Regional Government of Bolmut Regency, North Sulawesi Province, the study population was the whole object of the research studied, namely all civil servants in Bolmut Regency, North Sulawesi Province, the number of samples in this study were 160 employees in determining the sample used proportional random sampling technique. Data collection methods are primary and secondary, primary data is data obtained directly from the distribution of questionnaires to respondents in the District Government of Bolmut as research samples and secondary data, namely supporting data in the form of documents and interviews obtained from the research location. The data is collected through the distribution of questionnaires that are rated and tabulated for later analysis and the answers obtained by respondents in accordance with the predetermined variable values will then be analyzed using the help of SPSS software. The results showed that the variables of leadership and organizational culture had a positive and significant effect on employee job satisfaction.